Warfarin-Associated Diaphragmatic Hernia: An Unusual Diagnosis - Cristina Vilhena; Cátia Gameiro; Cláudia Tomás; Antónia Santos; Raquel Ilgenfritz (Case Reports in Obstetrics and Gynecology)
Fetal warfarin syndrome is a consequence of maternal intake of warfarin during pregnancy and comprises a wide range of manifestations, including some typical facial dysmorphologic features. The authors report a case of prenatal ultrasonographic diagnosis of warfarin embryopathy in an obese woman on unsupervised warfarin prophylaxis at the 16th week of gestation. The fetus presented with facial dysmorphism, pectus excavatum, diaphragmatic hernia, and pulmonary hypoplasia. To the best of our knowledge, this is the second reported case of warfarin-associated diaphragmatic hernia.